A numerical study on defect densities of double absorber CH3NH3PbI3/CIGS solar cell. (2022) - Mohanty, Ipsita; Mangal, Sutanu; Singh, Udai P.
Highlights: Numerical simulation of double-absorber heterojunction CH3 NH3 PbI3 /CIGS solar cell using SCAPS-1D. Device performance is optimized on studying the influence of defect densities. The optimized device shows the highest efficiency of 28.15%. Abstract: Numerical simulation of a solar cell with double absorber layers has been done using SCAPS-1D software. The use of two absorber layers minimises the implement of a hole transporter in the present work. Lead-based perovskite structure Methylammonium lead iodide (CH3 NH3 PbI3 ) and Copper Indium Gallium Selenide (CIGS) are used for simulation. An investigated study of impact of defect densities of the absorber layers as well as the interface has been done. The model Au/CH3 NH3 PbI3 /CIGS/TiO2 /ZnO:Al yields an efficiency of 28.15%. This device also obtains an enhanced fill factor of 78.44%. This device model can undergo fabrication process for research purposes.